2021
DOI: 10.1371/journal.pone.0253245
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated mutagenesis of sweet basil candidate susceptibility gene ObDMR6 enhances downy mildew resistance

Abstract: Sweet basil (Ocimum basilicum) is an economically important allotetraploid (2n = 4x = 48) herb whose global production is threatened by downy mildew disease caused by the obligate biotrophic oomycete, Peronospora belbahrii. Generation of disease resistant cultivars by mutagenesis of susceptibility (S) genes via CRISPR/Cas9 is currently one of the most promising strategies to maintain favored traits while improving disease resistance. Previous studies have identified Arabidopsis DMR6 (Downy Mildew Resistance 6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“… The grapevine DMR6 and DLO protein family. ( A ) Multiple alignment of grapevine DMR6 and DLO proteins with Zea mays ZmFNSI (NP_001151167) [ 40 ], Hordeum vulgare HvDMR6 (KAE8782493.1) [ 41 ], Solanum lycopersicon SlDMR6-1 (Solyc03g080190) and SlDMR6-2 (Solyc06g073080) [ 13 ], Solanum tuberosum StDMR6 (XP_006347521) [ 15 ], Ocimum basilicum ObDMR6 (QWT44767.1) [ 17 ], Musa acuminata MusaDMR6 (XP_009389864.1) [ 16 ], Arabidopsis thaliana AtDLO1 (At4g10500), AtDLO2 (At4g10490), and AtDMR6 (AT5G24530) [ 11 ]. The alignment is coloured with the default ClustalX colour scheme according to the amino acid chemical properties.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“… The grapevine DMR6 and DLO protein family. ( A ) Multiple alignment of grapevine DMR6 and DLO proteins with Zea mays ZmFNSI (NP_001151167) [ 40 ], Hordeum vulgare HvDMR6 (KAE8782493.1) [ 41 ], Solanum lycopersicon SlDMR6-1 (Solyc03g080190) and SlDMR6-2 (Solyc06g073080) [ 13 ], Solanum tuberosum StDMR6 (XP_006347521) [ 15 ], Ocimum basilicum ObDMR6 (QWT44767.1) [ 17 ], Musa acuminata MusaDMR6 (XP_009389864.1) [ 16 ], Arabidopsis thaliana AtDLO1 (At4g10500), AtDLO2 (At4g10490), and AtDMR6 (AT5G24530) [ 11 ]. The alignment is coloured with the default ClustalX colour scheme according to the amino acid chemical properties.…”
Section: Figurementioning
confidence: 99%
“…Together, these results suggest different functions of DMR6 homologs. In addition, recent works proved the role of DMR6 in susceptibility to Xanthomonas wilt in banana [ 16 ] and to Peronospora belbahrii in sweet basil [ 17 ], suggesting a widely conserved function across the plant kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…This will ultimately result in the development of pea genotypes having wider PM resistance for more number of pathogen races [ 132 ]. Recently, the genome editing has been undertaken for the Mlo locus to achieve the resistance in different crops including wheat [ 138 ], grapevine [ 139 ], tomato [ 140 ] and sweet basil [ 141 ].…”
Section: Durable Resistance Strategies For Pm Resistancementioning
confidence: 99%
“…Improving resistance to citrus canker has been an important citrus breeding objective (Gmitter and Talon, 2008). Recent studies have shown that disabling disease susceptibility ( S ) genes including DOWNY MILDEW RESISTANCE 6 ( DMR6 ) can be a promising approach to engineering durable and broad-spectrum resistance to bacterial pathogens (de Toledo Thomazella, et al ., 2021; Hasley, et al ., 2021; Kieu, et al ., 2021; Tripathi, et al ., 2021).…”
Section: Figurementioning
confidence: 99%